METODE PEMBELAJARAN SAS UNTUK MENINGKATKAN KETERAMPILAN MEMBACA SISWA KELAS I SD NEGERI 021 SITORAJO KARI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Emgusnadi Emgusnadi (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
Reading learning in the low grade class 1, which is often done in the early stages of learning which is calledpreliminary reading, has been done in various ways so that students read smoothly, but the numbers of studentswho cannot read in grade 1 are high. Therefore, researchers conducted research to improve reading skills ingrade 1 elementary school students by using the SAS learning method. . The research class study is improvementstudying process to solve problem that can be happen by a teacher in the class. Data on gain after research toteacher activity in cycle I meeting 1 with percentage 58%, meeting 2 with percentage 70,5%, in cycle II meeting3 percentage in the amount of 84%, and meeting 4 percentage obtained 97%. The student observation data inthis research obtained percentage in cycle I meeting 1 in the amount 51,5%, meeting 2 in the amount 66,5%, inthe cycle II meeting 3 in the amount 89%, and inthe meeting 4 obtained percentage in the amount 94% this isprove if the student activity is rise experience. Data increase learning outcomes in the class I SDN 021 SitorajoKari kecamatan Kuantan Tengah in the data early obtained average 60,5, in the daily test 1 obtained average inthe amount 74, and in the daily test 2 obtained average in the amount 83 this prove using the method of SAS theefective reading study used in class I.